Dampak Globalisasi Terhadap Penggunaan Bahasa Indonesia pada Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Syafrizal, Ridho; Nurhayati Pardosi, Juli; Ritonga, Mhd Verdi; Rimhot Rumapea, Tiopan; Roro Sekar Daniswari Ardiningrum, Raden; Rosmaini (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research is a quantitative research with an observation and interview approach as well as data collection through Google Form media. The sample size was set at 50 respondents, where the sample object was a student of the Faculty of Economics, State University of Medan. This study aims to find out how Globalization has an impact on the use of Indonesian Language on students of the Faculty of Economics at Medan State University, find out how globalization can affect students' language habits, and add wider insights related to the topics discussed. In this study, five question instruments were used to collect data from the topics discussed by the authors. The author asks these five questions to the resource person directly through Google Form media to make it easier for the resource person to respond to the question instrument provided by the author. The results of the study show that globalization affects the use of Indonesian among students of the Faculty of Economics at Medan State University. From the data obtained from the results of the study, it was explained that 72% or 36 respondents stated that they were quite influenced by globalization on the way respondents used Indonesian, then 22% or 11 respondents stated that they were greatly influenced by globalization on the way respondents used Indonesian and 6% or 3 respondents stated that they were not affected by globalization on the way respondents used Indonesian. This can be interpreted that in the era of globalization, the existence of the Indonesian language among students is declining.